Character Building Based on Pancasila Student Profile at MTs Negeri 2 Demak - Puteri, Gitsha Savera; Atmaja, Hamdan Tri; Gunawan, Gunawan (JESS (Journal of Educational Social Studies), 2025)
The Merdeka Curriculum aims to form and develop the character of students in accordance with the character values of the Pancasila dimension, believing and being devoted to God Almighty and having noble morals, global diversity, mutual cooperation, independence, critical thinking, and creativity. The aim of this study was to determine the formation of the character profile of Pancasila students in the learning process at MTs Negeri 2 Demak and to determine the resources supporting Character building in MTs Negeri 2 Demak which was analyzed using behavioristic theory by Edward Thorndike. This study uses a qualitative approach with a case study research type, while data sources are collected from informants selected using purposive sampling through observation, interviews and document studies. This study conducted at MTs Negeri 2 Demak. The research findings showed that Character building based on the Pancasila student profile has not been fully achieved in the habituation process and learning process, students pay less attention and apply good character to life due to lack of motivation from within and from outside themselves. Resources in supporting Character building are also not optimal, as evidenced by the lack of improvement in the quality of teacher human resources and infrastructure that have not been fully met.